Influencing Factors of Interfacial Behavior between Geogrid and Coal Gangue - Xiangxi Fan; Pengfei Gao; Weichao Liu; Lingxiao Meng; Yingdong Xu; Hong Zheng (Advances in Civil Engineering)
Coal gangue is a type of solid waste that is generated in the process of coal mining and washing. This concept can be effectively used in reinforced engineering fillings. The influences of shear rates and geogrid transverse ribs were studied using a large indoor direct shear test. The test results showed that the relationship between shear stress and shear displacement of geogrid-coal gangue is nonlinear, and the shear process is accompanied by the crushing of coal gangue particles. The addition of geogrid significantly improved the shear stress and interfacial quasi-cohesion of geogrid-coal gangue, whereas the interfacial quasi-friction angle remained almost unaffected. When normal stress was greater than 25 kPa, the shear stress gradually increased as the shear rate was increased from 1 to 5 mm/s. With an increasing shear rate, the interfacial quasi-friction angle increased, whereas the interfacial quasi-cohesion decreased. The interfacial shear stress, interfacial adhesion, and interfacial friction angle decreased with the number of geogrid ribs; the contribution of the middle transverse rib to the interfacial shear strength was smaller than that of the transverse rib at the far end in the shearing direction.